Determinants of Declining Water Quality - Ayana, Essayas (World Bank, Washington, DC, 2020)
This is a background paper for "Quality Unknown: The Invisible Water Crisis." (Report No. 140973)This review examines determinants of poor water quality and natural and anthropomorphic factors determining water quality. It also discusses various water quality parameter measurement tools that can be applied in situ or remotely to assess water quality easily so measurements can be used to evaluate the economic impact of poor water quality. The correlation of water quality indicators to determinants (natural or anthropogenic) is also summarized based on the abundance of literature supporting the relationship. In doing so, this paper takes a thematic approach and applied the following search phrases to the literature review: "determinants of (parameter) in surface water," "drivers of (parameter) in surface water," and "remote sensing techniques to estimate (parameter)."